The Influence of Understanding the Philosophy of Science on Students' Critical Attitudes and Academic Ethics in the Learning Process - Zilla, Lina; Rera Oktariya.S; Darwin Effendi (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
This study investigates the influence of understanding the philosophy of science on students’ critical attitudes and academic ethics in the learning process. Philosophy of science is essential in shaping systematic and reflective scientific thinking, while also serving as a foundation for academic character development. Using a quantitative approach, the research involved 30 postgraduate management students at Universitas PGRI Palembang. Data were collected through a closed-ended questionnaire using a five-point Likert scale to measure three constructs: understanding of the philosophy of science, critical attitude, and academic ethics. Analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results show that understanding the philosophy of science has a positive and significant effect on students' critical attitudes. Students with deeper understanding demonstrate better logical, analytical, and reflective thinking. Moreover, it significantly influences academic ethics—those with philosophical awareness tend to uphold academic integrity and originality. These findings affirm that the philosophy of science serves not only as a conceptual framework but also as a tool for shaping students’ intellectual and moral qualities. The study emphasizes the importance of integrating philosophy of science into higher education curricula to foster critical thinking and ethical academic behavior among students